FACTORS DETERMINING THE QUALITY MANAGEMENT OF HIGHER EDUCATION: A CASE STUDY AT A BUSINESS SCHOOL IN INDONESIA - Eliot Simangunsong (Jurnal Cakrawala Pendidikan, 2019)
Despite the facts that higher education institutions are the source of quality concept and theory, they have been lagging behind manufacturing or service businesses in embracing and carrying out proper quality management. Managing quality in higher education is a difficult task due to several factors such as different perspectives between stakeholders and traditional characteristics of institutions. On the other hand, accreditation, for example by the Indonesian Bureau of Higher Education Accreditation, and international accreditation bodies, such as AACSB, EQUIS, is perceived as a tool to demonstrate a certain quality threshold.  However, many studies argue that periodic quality assessments using recognized accreditation bodies do not touch inherent quality issues in education, and that they are generally used as an exercise of quality control. The objective of this study is to look beyond quality assessments using these recognized accreditation bodies and examine dimensions of quality from university's stakeholder’s point of view, especially the stakeholder that represents the demand side. Factor analysis is conducted, and the number of factors proposed by the results are identified. There are seven quality dimensions that have impacts on the quality management system in higher education. Three dimensions are new findings, i.e., the importance of providing health and insurance, the importance of good ambiance of campus environment, and stakeholder’s explicit ability to demonstrate quality in higher education.